Determinan Keputusan Investasi Deposito Pada Nasabah Bank Syariah Indonesia - Friska Efia Akwila; Adi Mansah (Yayasan Darussalam Patalassang, 2026)
This study analyzes the role of Islamic financial literacy, trust in Islamic banks, and product usage experience in determining sharia deposit investment decisions among Bank Syariah Indonesia (BSI) customers. Using a quantitative causal-associative approach, 111 BSI customers in South Tangerang who had used or were using sharia deposit products were selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. These findings indicate that customers' actual experience with sharia bank products and services is the most dominant factor, more influential than cognitive knowledge or trust alone. A tawhidic reflection on these findings affirms that an investment decision represents an effort (ikhtiar) to safeguard entrusted wealth (amanah), grounded in spiritual awareness rather than rational considerations alone. The study recommends strengthening service quality and digital customer experience as the primary strategy for increasing participation in sharia deposit investment.